A Matter of Judgment: Politics, Law and the Trial of Bishop Thomas Watson. (June 2015) - Paley, Ruth
<x xml:space="preserve">Abstract</x> Thomas Watson's controversial expulsion from the bishopric of St David's – and hence from the house of lords – after a long and bitterly‐fought series of legal actions, raised fundamental and difficult questions about the right to control membership of the house of lords and about the relationship between politics and the law, as well as between church and state. This article explores both the local and the national political contexts that prompted Watson's ordeal, suggesting that subsequent demonisation by Gilbert Burnet has obscured the extent to which Watson was the casualty of William III's determination to cow his political opponents. It concludes that Watson was marked out for opprobrium precisely because, like Sir John Fenwick, his political and social insignificance enabled him to be victimised without risking a backlash of opposition from the social and political elite.